Consumer Preferences of the Surabaya Community towards MP-ASI Premixed Rice : Preferensi Konsumen Masyarakat Surabaya terhadap Beras Premiks MP-ASI - Pradana Misbach, Mochamad Harits; Yulistiani, Ratna; Priyanto, Anugerah Dany; Fitriani, Awanda Winar (Jurnal Pangan dan Agroindustri, 2025)
Abstract Surabaya is one of the places for producers who provide MP-ASI products with various attributes, one of these products is MP-ASI premixed rice. This study aims to find out some of the attributes with the highest importance value for consumers in choosing MP-ASI premix rice products and identify consumer preferences on the sub-attributes of MP-ASI premix rice products. The attributes used in this study were cooking time, the type of material, the type of packaging, the addition of nutrients, the flavor variant, and the place of purchase. The research was carried out using a survey method. The total number of respondents was 100 that determined using the Slovin formula, and the collection of respondents was carried out using a two-stage cluster sampling technique. The premixed rice MP-ASI products that are the preference according to consumers are made from white rice (0,24) with the addition of fat nutrients (0,41), have a type of plastic bottle packaging (0,06) with a cooking time of less than 20 minutes (0,34), and have a variant of fish meat flavor (0,16) which is sold online (0,14). The results of the consumer preference analysis from this study can be used as a consideration in developing premix rice MP-ASI products.   Abstrak Surabaya adalah salah satu tempat bagi produsen yang menyediakan produk MP-ASI dengan berbagai atribut, salah satu produk tersebut adalah beras premiks MP-ASI. Tujuan dari penelitian ini adalah untuk menentukan beberapa atribut dengan nilai kepentingan tertinggi bagi konsumen dalam memilih produk beras premiks MP-ASI serta mengidentifikasi preferensi konsumen pada sub-atribut produk beras premiks MP-ASI. Penelitian dilaksanakan menggunakan metode survei, total jumlah responden adalah 100 ditentukan menggunakan rumus Slovin, dan pengambilan responden dilakukan dengan teknik two-stage cluster sampling. Produk MP-ASI beras premiks yang menjadi preferensi menurut konsumen yaitu berbahan dasar beras putih (0,24) dengan penambahan nutrisi lemak (0,41), memiliki jenis kemasan botol plastik (0,06) dengan waktu tanak kurang dari 20 menit (0,34), dan memiliki varian rasa daging ikan (0,16) yang dijual secara online (0,14). Hasil analisis preferensi konsumen dari penelitian ini dapat dijadikan pertimbangan dalam mengembangkan produk MP-ASI beras premiks.